2019
DOI: 10.3390/ijgi9010001
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Hazard Modeling for Simulating Torrential Stream Response to Flash Flood Events

Abstract: This study aims to monitor the flash flood response of Vidor/Wadore hill torrent in Pakistan by the integration of Personal Computer Storm Water Management Model PCSWMM (hydrologic) and HEC-RAS 5.x (hydraulic) models. The method leverages remote sensing and GIS derive estimates of measured and inferred parameters of Vidor rural catchment to quantify the flash flood events of the last four years: 2014–2017. The calibration of the PCSWMM is performed using the sensitivity-based radio tuning calibration (SRTC) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…The Hydrological Engineering Center River Analysis System (HEC‐RAS) is used around the world for flood depth and hazard prediction (e.g., Stoleriu et al 2019; Munir et al 2020). A digital elevation model (DEM) with a horizontal resolution of 0.5 m and a vertical resolution of 1 m were imported as a terrain layer into RAS Mapper, part of HEC‐RAS 5.0.7.…”
Section: Methodsmentioning
confidence: 99%
“…The Hydrological Engineering Center River Analysis System (HEC‐RAS) is used around the world for flood depth and hazard prediction (e.g., Stoleriu et al 2019; Munir et al 2020). A digital elevation model (DEM) with a horizontal resolution of 0.5 m and a vertical resolution of 1 m were imported as a terrain layer into RAS Mapper, part of HEC‐RAS 5.0.7.…”
Section: Methodsmentioning
confidence: 99%
“…The major torrents affecting D. G. Khan include Kaura, Vehowa, Sanghar, Sori Lund, and Vidor. The characteristics of torrents including; variation in peak flows, and high sediment yield hardened the management of these torrents [3]. The steep slope mountainous catchment is primarily majorly composed of loam, clay loam, and sandy clay loam.…”
Section: Study Areamentioning
confidence: 99%
“…The stream locally named "Rod Kohi" is categorized as non-perennial and remains active in monsoonal season. The total length of the torrential stream is approximately 158 km [3,4,34]. The discharge data (Table 1) collected from Punjab Irrigation Department (2010-2019) shows that event concentration is clustered in the monsoon season (June, July, and August).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The model assessment results in Wu et al [22] showed that the integration of spatio-temporal GIS and hydrodynamic models can improve the efficiency of flood risk simulations for decision support, such as dam-break flood simulations and dynamic visual simulations. Munir et al [23] integrated a hydrological model and a hydraulic model based on remote sensing and GIS-derived estimates to simulate torrential streamflow response to flash flood events in Pakistan. The study made use of the integration of GIS and remote sensing technique to derive different hydrological parameters for the models at a pixel level.…”
Section: Content Of the Special Issuementioning
confidence: 99%